Infection by mycotoxigenic fungal species and mycotoxin contamination of maize grain in Umbria, central Italy - Covarelli, Lorenzo; Beccari, G.; Salvi, S. (Pergamon, 2011)
Surveys were carried out in 2006 and 2007 in Umbria (central Italy) to evaluate the presence of mycotoxigenic fungi and mycotoxins in maize grain sampled at harvest. Fusarium spp., were the most abundant species detected in maize kernels, followed by Aspergillus species of sections Flavi and Nigri and by Penicillium spp. Among Fusarium species, F. verticillioides was the most prevalent species, as detected by PCR directly on the kernels and on the fungi isolated from the kernels, followed by F. proliferatum and F. subglutinans. Fumonisins were the predominant mycotoxins with values, on average, of 4.3 and 5.7mgkg -1 , in 2006 and 2007, respectively, with a maximum of 76.3mgkg -1 in the second year. Deoxynivalenol ranged from 0.2 to 3.98mgkg -1 in 2006 (average 1.04mgkg -1 ) and from undetectable levels to 14mgkg -1 in 2007 (average 0.86mgkg -1 ). Aflatoxins, analyzed only in 2007, averaged 26.3µgkg -1 , with a maximum of 820µgkg -1 . Zearalenone content was always very low. Results indicate that EU legal limits for these mycotoxins were rarely exceeded with low levels across most of the examined area, suggesting that this region could be considered suitable for the production of healthy maize. © 2011 Elsevier Ltd.